How does the Cigarette Company Deal with the Rise of Illegal Cigarette Products - Husni F Ramadhan; Joseph MJ Renwarin; M Richo Rianto; Djuni Thamrin; Matdio Siahaan; Dwi Entia; Silvia A Chairunnisah; Annisa D Ambarwati; Hendy Tannady (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
The phenomenon of the rise of illegal cigarette products in Bekasi poses a problem for cigarette companies. The reason is that these illegal cigarettes do not use excise tapes or use fake excise tapes that are detrimental to cigarette companies or the government. The trade in illegal cigarette products does not have a circulation permit among the community. This study aims to find the influence of price and product packaging suitability on consumer purchase decisions on illegal cigarette products in East Bekasi. The method used was a quantitative approach with pre-survey results of 20 respondents. With the final survey results, 100 respondents were collected through google form using a data collection technique, namely purposive sampling. The statistical data processing used is Structural Equation Modeling Partial Least Square (SmartPLS). In combating illegal cigarette products, continuous efforts are needed and finding the right innovations in order to break the circulation of illegal cigarettes in the community. Such as strengthening regulations in collaboration with the government and law enforcement agencies. Tightening supervision of cigarette products circulating in the community. Some implications for cigarette companies such as issuing new innovations for the community to increase competitiveness in the market. A marketing campaign that promotes the importance of legality that can affect a cigarette product. A significant contribution to the literature on cigarette companies in this study is to look at business strategies from the perspective of cigarette companies in terms of dealing with the rise of illegal cigarette products. This study provides a new insight into policies that can be used into effective plans to reduce the circulation of illegal cigarettes while maintaining business sustainability.